Three “pitfalls” for the unwary: Third-party funding in Asia - CHAN, Darius (Institutional Knowledge at Singapore Management University, 2018)
For some time, practitioners would have seen news alerts headlining that third-party funding is permitted in Singapore and Hong Kong for arbitration and arbitration-related court proceedings. Digging a little deeper beyond the shiny new labels, this article highlights three practical “pitfalls” which practitioners would have to be mindful of when dealing with third-party funding in Singapore and Hong Kong.